Eradicating Corruption and Effective Legal Action at the Bondowoso Prosecutor's Office, East Java - Ansori; Firman, Edy; Zikra, Alfiandi; Abrari, Achmad; Budilaksono, Agung (PT Inovasi Pratama Internasional, 2024)
Eradicating corruption has become the main focus in many countries, including Indonesia, because of its disturbing economic, social and political impacts. The Prosecutor's Office, as a law enforcement agency, has an important role in this effort. This research proposes to increase the effectiveness of legal actions taken by the Bondowoso Prosecutor's Office, East Java, in eradicating corruption. The approach to eradicating corruption involves various policies, as confirmed by the National Strategy for Eradicating Corruption (SNPK). However, it is also important to involve the role of students and crime policy and corruption prevention. This research will analyze the context of Bondowoso Regency, East Java, as well as research on the relevance of efforts to eradicate corruption at the local level, especially focusing on the role of the Prosecutor's Office. The Document Analysis method is used in this research to initiate policies and legal actions that have been taken by the Bondowoso Prosecutor's Office. Analysis steps include collection, selection, analysis and interpretation of relevant documents. The results of this analysis will help identify policies that have been implemented, measure their effectiveness, and identify the challenges faced. Research results and discussions include collection, selection, analysis and interpretation of documents. Policy identification, effectiveness evaluation, challenge identification, and recommendations for improvement are part of the conclusions of this research. Thus, this research provides a deeper understanding of the efforts to eradicate corruption by the Bondowoso Prosecutor's Office, East Java. It is hoped that the results can provide a basis for improving policies and practices for eradicating corruption at the local level, as well as making a positive contribution in eradicating corruption more effectively.